2014
DOI: 10.3126/ajms.v6i2.11099
|View full text |Cite
|
Sign up to set email alerts
|

Hepatic encephalopathy in chronic liver disease; predisposing factors in a developing country

Abstract: Objective: To find out the risk factors for developing Hepatic Encephalopathy in patients suffering from Chronic liver disease.Background: Hepatic encephalopathy (HE) is a neuropsychiatric disorder that is caused by liver damage.  In its pathology, alterations in normal brain function are associated with an increase in blood ammonia, benzodiazepine like substances, products of neurotoxic fatty acids, and other gut derived toxins, which gain access to the brain as a result of liver dysfunction. Study Design: Ho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

6
2
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(11 citation statements)
references
References 9 publications
6
2
0
Order By: Relevance
“…Similar were the findings in many studies by Raphael et al 8 , Sethuraman et al 9 , Mumtaz et al 12 , Singh et al 13 and Nayak et al 14 where majority of cirrhotic patients with encephalopathy were observed in Child class C.…”
Section: Bar Diagram 1: Age Groups /Sex Distribution Of Patients Under Studysupporting
confidence: 90%
See 4 more Smart Citations
“…Similar were the findings in many studies by Raphael et al 8 , Sethuraman et al 9 , Mumtaz et al 12 , Singh et al 13 and Nayak et al 14 where majority of cirrhotic patients with encephalopathy were observed in Child class C.…”
Section: Bar Diagram 1: Age Groups /Sex Distribution Of Patients Under Studysupporting
confidence: 90%
“…The proportion of grade I, II, III, IV HE were 22.1 %, 36.5%, 25% and 16.4% respectively. The majority of cases were in grade III and II in the study by Sethuraman et al 9 Similar were the findings in the studies by Kumar et al 10 Mumtaz et al 12 ,Singh et al 13 and Poudyal et al 15 Contrary to above studies, majority (36%) of the patients were in grade IV HE followed by 30% in grade III ,10% in grade II and 24% had grade I HE in the study by Nayak et al 14 In the current study, majority of 65% patients were of Child class C. This was followed by 30 % patients in Child class B and 5% patients in Child class A.…”
Section: Bar Diagram 1: Age Groups /Sex Distribution Of Patients Under Studysupporting
confidence: 82%
See 3 more Smart Citations